Failure of IGF-I and IGFBP-3 to diagnose growth hormone insufficiency. Issue 5 (1st May 1999) - Mitchell, H; Dattani, M T; Nanduri, V; Hindmarsh, P C; Preece, M A; Brook, C G D
Abstract : BACKGROUND: Growth hormone insufficiency (GHI) is diagnosed conventionally by short stature and slow growth, and is confirmed by diminished peak GH response to a provocation test. Insulin-like growth factor I (IGF-I) and IGF binding protein 3 (IGFBP-3) have previously been considered individually OBJECTIVE: To test the hypothesis that the combined analysis of IGF-I and IGFBP-3 could act as a surrogate marker for the diagnosis of GHI. DESIGN: Reference ranges for IGF-I and IGFBP-3 were calculated using 521 normal individuals. A retrospective analysis was performed on 318 children referred for investigation of short stature. RESULTS: No significant difference was found between either the IGF-I or IGFBP-3 standard deviation scores (SDSs) in children with and without GHI. If the requirement were for both tests to be positive (< −2 SDS) for a diagnosis of GHI, then 99% of children without GHI would be correctly identified; however, the sensitivity of the test was only 15%. CONCLUSIONS: Neither IGF-I nor IGFBP-3 alone is a marker for GHI. In addition, they cannot be used as an effective screening test in combination.